Growth and Yield of Soybeans in Various Growing Media Composition and Inoculation of Rhizobacteria on Marginal Soils - Aditya Aris Kurniawan; Pauliz Budi Hastuti; Arif Umami (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Soybean is one of the leading commodities that is being developed in Indonesia. Today, the increase of soybean needs is not followed by its production capacity. Meanwhile, the area of productive land for soybean farming is decreasing due to land conversion for non-agricultural needs. One effort that can be an alternative is using marginal land by applying appropriate technology such as manure and biofertilizer. So that, it was necessary to know the composition of manure and biofertilizer, which was appropriate to increase the growth and yield of soybean plants on marginal soils. Complete Randomized Design was used in the experiment with two factors. The first factor was the ratio of manure: soil (v:v) there are 0:1, 1:1, 1:2, and 2:1. The second factor was rhizobacteria inoculum, which included without rhizobacteria, exogenous rhizobacteria, and indigenous rhizobacteria. Results showed that the composition of the best planting medium for growth and yield of soybean is manure: soil 1: 1 and 1: 2. The source of the rhizobacteria inoculum is not a significant difference to the soybean’s growth and yield. Manure and soil 1: 2 with indigenous inoculum tended to produce the best total number of nodules and effective root nodules. Manure and soil 1:1 with indigenous inoculum produce the best of seeds number. Manure and soil 1:2 or 2:1 with exogenous inoculum tended to produce the best seed index weight (g per 100 seeds).